Analysis of the Impact of Foreign Direct Investment: Solutions to the Indonesia Economy during The Covid-19 Pandemic (Faculty of Law Universitas Negeri Semarang, 2022)
Foreign investment is one of the crucial instruments for a country in promoting economic growth for the sake of creating public welfare. Indonesia as a country with abundant economic potential, requires foreign investors to solve problems, especially related to sustainable development and suppress the high unemployment rate. Legal reform in increasing the realization of foreign investment entering Indonesia is realized through the Omnibus Law in the Job Creation Act to create a good and healthy investment climate. The presence of Covid-19 has caused the country's economy to experience a significant decline. The presence of the Job Creation Act in accelerating foreign investment into Indonesia is expected to encourage the strengthening of the national economy after the Covid-19 pandemic. However, there are problems in its implementation caused by the guarantee of legal certainty in running business activities and overlapping regulations in business licensing. The research method used is normative legal research. This study uses the Statute approach. The technique of tracing legal materials uses library research techniques, and analysis of studies using qualitative analysis. The results of this study indicate that the Government has made maximum efforts by issuing various regulations or policies to revive the investment climate in Indonesia so that the country's economic growth can increase, and is able to provide legal certainty in doing business in Indonesia.